2007
DOI: 10.1186/1475-2875-6-110
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group system and placental malaria in an area of unstable malaria transmission in eastern Sudan

Abstract: Background: Understanding the pathogenesis of malaria in pregnancy and its consequences for both the mother and the baby is fundamental for improving malaria control in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
7
33
2
Order By: Relevance
“…At 95% and 99% confidence intervals, chi square statistical analysis carried out on data showed that male students were significantly more infected than the females. This finding is supported by the reports of some previous studies which stated that males were more vulnerable to malaria infection than females [74,12,69]. Finding is however, inconsistent with the report of some workers [34].…”
Section: Discussionsupporting
confidence: 66%
“…At 95% and 99% confidence intervals, chi square statistical analysis carried out on data showed that male students were significantly more infected than the females. This finding is supported by the reports of some previous studies which stated that males were more vulnerable to malaria infection than females [74,12,69]. Finding is however, inconsistent with the report of some workers [34].…”
Section: Discussionsupporting
confidence: 66%
“…As before, group O primiparae were at an increased risk of active placental malaria (OR, 2.18; P ϭ 0.02). Two other studies from Sudan (n ϭ 293) and Gabon (n ϭ 378) found no increased risk of malaria in group O primiparae but confirmed some protection against placental malaria in multiparous group O women (OR, 0.6) (326,327). No correlation between active malaria, placental malaria, parasitemia, parity, and ABO type was identified for 447 Myanmar refugees in western Thailand (328).…”
Section: Plasmodium Falciparummentioning
confidence: 88%
“…A few studies have examined the impact of ABO type on pregnancy, with most studies showing a selective advantage with group O (324)(325)(326)(327)(328). A small study of 198 Gambian mothers reported an inverse relationship between ABO type, malaria, and parity (324).…”
Section: Plasmodium Falciparummentioning
confidence: 99%
“…While placental malaria infections that were positive by histology were not associated with LBW, submicroscopic malaria infections were, and this was a statistically significant finding. In fact, the impetus for this study arose out of the knowledge that two cross-sectional studies in Eastern Sudan failed to show significant associations between LBW delivery and placental malaria infection, as diagnosed by histology [7,18]. The prevalence (28.0%) of histologically determined placental malaria infections in both groups (cases and controls) in the current study is similar to the prevalence of the placental malaria infections recently observed in Eastern and Central Sudan [7,18,23].…”
Section: Discussionmentioning
confidence: 99%